E-Learning Critical Success Factors from the Experience of Distance Learners of a Business Faculty in a Malaysian Public University - Omar, Muhamad Khalil; Ahmad, Mohamad Fahimi; Mamat, Rusalbiah Che; Ngadi, Nizar Kusyrina (Advances in Social Sciences Research Journal, 2021)
The motivation behind this investigation is to distinguish the Critical Success Factors of e-learning from the student perception in e-PJJ Program (distance learning programme) in Faculty of Business Management Universiti Teknologi MARA. The study depended on the quantitative research technique. The questionnaire was disseminated among e-PJJ student conveniently in Faculty Business Management. There are six courses involved, 1) BBA (Hons) Operation Management, 2) BBA (Hons) Marketing, BBA (Hons) Finance, 3) BBA (Hons) Human Resources Management, 4) BBA (Hons) International Business and 5) Bachelor in Office Management (Hons). The measure of investigation are factors that impact the achievement components of e-learning program in Faculty of Business Management.